LEGAL ANALYSIS OF CRIMINAL RESPONSIBILITY OF PERPETRATORS IN CLEARING LAND FOR OIL PALM PLANTATIONS IN PRODUCTION FOREST AREA (Study of Decision Number 56/ Pid.Sus /2024/PN ksn ) - Chettlin Benitha; Aristoteles; Louise Theresia; Joanita Jalianery (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
Cases involving defendant Ir. Sunarto Bin ( the deceased ) Supardi, who was accused open land in the area forest protected without permission , lifting issue law important related management forests and regulations use land in Indonesia. The defendant open land For plantation coconut palm oil in Production Forest Areas Permanent (HMP), which is regulated by law Forestry (Law No. 41 of 1999). This law arrange function forests and management land , prohibit activities that change function area forest without appropriate permission . This case clear show that violation main related with management area forest as arranged in the Forestry Law , not violation to activity operational business plantation as arranged in the Plantation Law (Law No. 39 of 2014). Forestry Law focused on conservation forests and use land sustainable , while the Plantation Law discusses things technical in operation plantation like licensing , use land and management environment . In case this , action defendant in a way direct violating the Forestry Law , especially Because land used​ For plantation the is part from area forest protected . Situation This highlight importance limitation strict laws​ in use land forests and their necessity get agreement government in a way explicit before change land status forest protected For objective agriculture . With compare second Constitution this case​ This underline the need stricter enforcement of Forestry Law effective For prevent deforestation illegal and ensure practice management forest sustainable followed . Findings this also shows How gap law in protection forest Keep going hinder protection the right environment although there is relevant laws .​